Pengembangan Kompetensi Guru Bahasa Inggris Madarasah Aliyah dalam Penyusunan Modul Ajar Kurikulum Merdeka: Improving the Competence of Madrasah Aliyah English Teachers in Preparing Learning Modules of Kurikulum Merdeka - Hartono, Hartono; Anwar, Choiril; Nugroho, Kurniawan Yudhi; Abidin, Zaenal (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Despite being introduced in February 2022, many teachers still need help applying the Independence curriculum at their schools. Many teachers must be more experienced in implementing the curriculum and require additional time to comprehend its ideals and essence fully. The community service program aimed to enhance teachers' proficiency in creating and composing instructional modules for the Independence Curriculum. The program participants were English instructors from Madrasah Aliyah in the Demak Regency, who were members of the Demak English Teacher Association of Madrasah Aliyah. The program was divided into three phases: pre-face-to-face training, face-to-face training, and post-face-to-face training consultation and help. A questionnaire gathered data on the subjects and interviews with select association members before in-person training. During the in-person training, the Community Service team engaged with the teachers by presenting educational materials, facilitating discussions, and giving participants exercises. The instruction was placed at Madrasah Aliyah Demak for a single day. Observations throughout the training revealed that numerous English teachers needed a complete understanding of teaching modules, resulting in their inability to develop and write them effectively. Following the training, the Community Service Teams offered consultations and assistance to the teachers to support them in finishing the modules. Teachers encountered persistent challenges, indicating the need for additional training.